2000
DOI: 10.1111/j.1469-1795.2000.tb00235.x
|View full text |Cite
|
Sign up to set email alerts
|

The conservation value for birds of cacao plantations with diverse planted shade in Tabasco, Mexico

Abstract: We surveyed birds in cacao (Theobroma cacao) plantations in the state of Tabasco, Mexico. The shade canopy was planted by farmers and consisted of approximately 60 species of trees with no single dominant species. Canopy height averaged 15 m and the structure was multi-storied. We conducted 220 ten minute, 25 m radius point counts for birds and detected 1550 individuals from 81 species. The average number of birds/point and the expected diversity in a fixed number of individuals within the cacao surveyed were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(58 citation statements)
references
References 14 publications
4
51
0
3
Order By: Relevance
“…between 15 and 20%) of the original basal area and forest tree species should be maintained. Five to eight years of fallow period should also be essential in order to create temporal favourable microclimatic conditions suitable to attract many forest bird species (Lawton et al, 1998;Greenberg et al, 2000;Daily et al, 2001;Hughes et al, 2002;Waltert et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…between 15 and 20%) of the original basal area and forest tree species should be maintained. Five to eight years of fallow period should also be essential in order to create temporal favourable microclimatic conditions suitable to attract many forest bird species (Lawton et al, 1998;Greenberg et al, 2000;Daily et al, 2001;Hughes et al, 2002;Waltert et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…The Ngomedzap area is considered by cocoa farmers to be less technified (more dense and diverse shade, fewer chemical inputs) and could be compared to the ''rustic'' cocoa areas (Greenberg et al 2000) reported in Latin America. The Kedia and Talba areas are considered to be more technified (less dense and diverse shade, high-chemical inputs) and are seen as the pioneer front in cocoa cultivation in southern Cameroon.…”
Section: Study Sitesmentioning
confidence: 99%
“…Their management practices are influenced by their relationship to the other components of the land-use system and are oriented at using a combination of multiple forest resources (Sonwa et al 2001;Schroth et al 2004;Perfecto et al 2005). Their adaptive nature offers options for combining biodiversity conservation and production for human benefits (Greenberg et al 2000;Reitsma et al 2001;Perfecto et al 2004;MCNeely and Schroth 2006;Gordon et al 2007;). TFGs are developed as a result of the interactions between local communities and forests and reflect various forms of human creativity in dealing with forest resources.…”
Section: Introductionmentioning
confidence: 99%
“…Within the agroforestry literature, the agronomic and biophysical aspects of such systems have received a disproportionate attention compared to the socioeconomic features (Nair, 1999), a situation which persistsespecially in the case of coffee 1 (Coffea arabica). The voluminous literature related to ecological features in shaded coffee (and cacao) systems (Beer et al, 1998) contrasts sharply with the few, but emerging, studies on such systems' socioeconomic contribution to producers' livelihoods-with those being nearly restricted to African countries (Leakey et al, 2005;Gockowski et al, 1997;Awono et al, 2002;Ndoye et al, 1997) Recent academic interest in managed lands as potential habitat reveals the ecological and conservation value of shaded cropping systems as refuges for wildlife and/or areas capable of providing ecological services (Mas and Dietsch, 2004;Wunderle and Latta, 1996, 2000Perfecto et al, 1996;Greenberg et al, 1997Greenberg et al, , 2000Rice and Greenberg, 2000;Rice and Ward, 1996;Sherry, 2000;Roubik, 2002;Ricketts, 2004;Philpott, 2005;Solis-Montero et al, 2005;Pineda et al, 2005). Many of these studies focus on shade coffee.…”
Section: Introductionmentioning
confidence: 99%